THE STUDY OF THE LOAD FLOW AFTER THE ADDITION OF MOUTONG’S MAIN SUBSTATION IN THE ISOLATED SYSTEM OF KOTARAYA - Alfira, Wisna Saputri; Su, Vania Amelinda; Aksan, Aksan (Jurnal Teknologi Elekterika, 2025)
PT. PLN (Persero) UP3 Tolitoli consists of four customer service units, namely ULP Leok, ULP Bangkir, ULP Moutong, and ULP Kotaraya. The electricity supply in ULP Kotaraya comes from an isolated system supported by PLTD Kotaraya, PLTD Tomini, and PLTD Palasa. During the dry season from September to November 2023, the power deficit at the power plants reached 950 kW, causing rolling blackouts. In order to overcome this problem, PLN UP3 Tolitoli plans to build a substation near Ongka Malino District to supply the Kotaraya system, which will improve flexibility and customer satisfaction. This study aims to implement the system condition through system testing based on the design of the Kotaraya isolated system after the operation of the Moutong Substation using software. The results of this study show that after the Moutong Substation operates, the functions of PLTD Kotaraya and PLTD Palasa change into voltage controllers, resulting in a power system with medium-voltage busbar voltage values that are more stable based on the standards used by PLN, with a nominal range of +5% and -10% against 20 kV.